The Role of Parents towards Early Childhood in the Process of Learning English in the Global Era - Latifa, Ammang (Jurnal Pendidikan Progresif, 2020)
The Role of Parents towards Early Childhood In the Process of Learning English in the Global Era. Objective: This research aims to find out parents’ perspectives about the importance of English learning and to know the involvement of parents in the process of learning English. Methods: Therefore, the Researcher provided two kinds of the procedure to collect data, namely 1) Questionnaire and 2) Interview as the quantitative and qualitative methods of this research. The sample consisted of 16 parents who have profession as the lecturer in Makassar Muhammadiyah University and Parepare Muhammadiyah University in Indonesia. Findings: this study showed that parents’ have a very positive perspective on the importance of teaching English to young learners. They enthusiastically support their children in the process of learning English as a foreign language for them, even though they agreed that there are some challenges they can face in this process.Keywords: parents role, early childhood, learning English.DOI: 10.23960/jpp.v10.i2.202003